2021
DOI: 10.1158/0008-5472.can-20-0652
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptional Regulatory Loop of Master Regulator Transcription Factors, PPARG, and Fatty Acid Synthesis Promotes Esophageal Adenocarcinoma

Abstract: Although obesity is one of the strongest risk factors for esophageal adenocarcinoma, the molecular mechanisms underlying this association remain unclear. We recently identified four esophageal adenocarcinoma–specific master regulator transcription factors (MRTF) ELF3, KLF5, GATA6, and EHF. In this study, gene-set enrichment analysis of both esophageal adenocarcinoma patient samples and cell line models unbiasedly underscores fatty acid synthesis as the central pathway downstream of three MRTFs (ELF3, KLF5, GAT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 57 publications
2
40
0
Order By: Relevance
“…The outcomes revealed that the high PPARG expression group had a higher level of immune checkpoint expression. These findings support PPARG as an additional biomarker for prognosis after immunotherapy and an additional target to facilitate corresponding immunotherapy ( Ding et al, 2020 ; Ma et al, 2021 ). However, in-depth studies are required to establish further facts.…”
Section: Discussionsupporting
confidence: 67%
“…The outcomes revealed that the high PPARG expression group had a higher level of immune checkpoint expression. These findings support PPARG as an additional biomarker for prognosis after immunotherapy and an additional target to facilitate corresponding immunotherapy ( Ding et al, 2020 ; Ma et al, 2021 ). However, in-depth studies are required to establish further facts.…”
Section: Discussionsupporting
confidence: 67%
“…As protein phosphorylation had been revealed to play vital roles in multiple cancers [37][38][39], we also analyzed the NOP2 phosphoprotein expression and found that it was highly expressed in primary ccRCC tumor than normal tissues with phosphorylation sites at the S58, T191 and S728. In order to identify NOP2-related signaling pathways, GSEA, as a useful tool, had been applied by various researchers [40,41]. Finally, five eligible signaling pathways were identified, containing cytokine-cytokine receptor interaction pathway, cytosolic DNA sensing pathway, glycerophospholipid metabolism pathway, primary immunodeficiency pathway, and intestinal immune network for IgA production pathway.…”
Section: Discussionmentioning
confidence: 99%
“…6P). This set of transcription factors has previously been shown to be operational in both Barrett's and OAC (Rogerson et al, 2019(Rogerson et al, , 2020Chen et al, 2020;Ma et al, 2021;Pan et al, 2020) and suggests that ERBB2 activation leads to at least partial suppression of their activity in OAC cells.…”
Section: Discussionmentioning
confidence: 72%
“…Opening regions showed 9 enrichment of motifs for a range of transcription factors which drive a gastro-intestinal programme in OAC including HNF4, GATA, FOXA, KLF and CEBP factors after 35 days (Fig. 4B; Supplementary Table 2; Rogerson et al, 2019;Chen et al, 2020;Ma et al, 2021;Pan et al, 2020). These events were already initiated after 1 day treatment (Supplementary Fig.…”
Section: Different Transcriptional Regulatory Pathways Are Associated With Chromatin Opening and Closing Eventsmentioning
confidence: 96%
See 1 more Smart Citation